Inovasi Pelayanan Publik melalui Aplikasi Marawa pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Solok - mercy vaguita (Jurnal Administrasi Publik dan Pemerintahan, 2026)
This study aims to explain public service innovations at the Population and Civil Registration Office in Solok Regency, thus facilitating public access to services. To date, poor service delivery has hampered the processing of administrative documents. This study employed qualitative methods, using interviews, documentation, and field observation as data collection techniques. The results indicate that the Marawa application innovation at the Solok Regency Population and Civil Registration Office has facilitated public service delivery. Thanks to the Marawa innovation, the Office received an award for compliance in public service delivery, with highly satisfactory results.